Social Networking Sites Use and Cross Cultural Adaptation of Muslim Indonesian Students in Australian Universities: Valuing Cultural Diversity - Imam Nuraryo (Program Studi Ilmu Komunikasi, 2014)
Muslim Asian students have diverse specific needs when undertaking education in western country universities. Many international students use social networking sites as media for distance communication and helping in their adjustment.This study attempts to investigate the impact of using new social networking sites on the cross cultural adaptation process. Qualitative methodology was used for the study. Individual in-depth interviews were conducted for data collection. The study investigates social networking uses and the adaptation experiences of 10 Muslim-Indonesian studying (or graduated) in some Australian universities.This research shows that most Muslim Indonesian students use them just to take information about Islam and instead of using them to publicize Islamic teaching (Da’wah). Social networking sites can help for establishing and maintaining relationship their friends in Indonesia, making adjustment, and sharing cultural experiences such as dealing with stereotype or looking for halal food and place for praying. Social networking sites are mostly used to share information and to discuss information about Islam and the way of Muslim adjusting in non Muslim environment.